1999
DOI: 10.1002/(sici)1520-6777(1999)18:1<17::aid-nau4>3.3.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

Repeated pressure‐flow studies in the evaluation of bladder outlet obstruction due to benign prostatic enlargement

Abstract: Test-retest reliability of repeated voids in pressure-flow studies and the influence on maximum flow rate (Q max pQ), detrusor pressure at maximum flow rate (p det Q max ), voided volume, and residual urine were studied. Also the agreement in interpretation of pressureflow tracings between investigators and a single blinded central reader acting as a quality control center (QCC) were assessed. In addition, correlations between p det Q max and patient age, International Prostate Symptom Score (IPSS), free maxim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 0 publications
1
18
0
1
Order By: Relevance
“…Severe complications during or after urodynamic investigation were reported in up to 19%, including urinary retention, gross hematuria, urinary tract infection, and fever [10]. Also there are studies in the literature that reported no association between invasive pressure flow parameters and the IPSS [11][12][13]. According to guidelines pressure flow studies are optional diagnostic tests for routine work-up of elderly men with LUTS [14][15].…”
Section: Discussionmentioning
confidence: 99%
“…Severe complications during or after urodynamic investigation were reported in up to 19%, including urinary retention, gross hematuria, urinary tract infection, and fever [10]. Also there are studies in the literature that reported no association between invasive pressure flow parameters and the IPSS [11][12][13]. According to guidelines pressure flow studies are optional diagnostic tests for routine work-up of elderly men with LUTS [14][15].…”
Section: Discussionmentioning
confidence: 99%
“…12 The symptomatic response to finasteride has been shown to be greater in prostates weighing more than 40 g. 13 However, the effect of finasteride on prostatic symptoms may be mediated by other factors than mere reduction in volume. The mechanism of action of phytoestrogens remains unclear, but at least one randomized double-blinded study reported nearly equal improvements in uroflow, symptom scores, and quality of life when compared to 5-alphareductase inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the studies were performed on patients without SCI. The largest trial was a prospective, multicenter trial including 216 men with lower tract symptoms caused by benign prostatic hypertrophy (7). The study evaluated the test-retest reliability of several urodynamic parameters during 3 voids and found no significant changes in various parameters, including maximum flow rate, volume voided, and residual volume.…”
Section: Discussionmentioning
confidence: 99%
“…There are several studies that support both shortterm and long-term reproducibility of urodynamic studies (7)(8)(9)(10)(11). However, there have been no studies specifically evaluating and documenting the variability of urodynamic tests.…”
Section: Introductionmentioning
confidence: 99%